Features of balance of proinflammatory and anti-inflammatory cytokines in newborns with herpes virus infections - Rakhmankulova, Zukhra (Medical and Health Science Journal, 2010)
The paper examines features of balance between proinflammatory and anti-inflammatory cytokines in newborns of mothers with herpes virus infections (SHV, CMVI). This investigation included 35 newborns, of them 10 were full-term newborns of healthy mothers (group 1 - umbilical blood); 10 - full-term newborns with various pathology of perinatal period in mothers with intrauterine infections (group 2 - umbilical blood); 15 practically healthy newborns of healthy mothers (control group - peripheral blood). The paper studies production of proinflammatory IL-1b, IL-8, γ-IFN and anti-inflammatory (IL-4) cytokines in newborns in norm and with intrauterine infections. The study has shown that the level IL-4 in the umbilical blood in newborns born from the mothers with intrauterine infection did not differ from a level in peripheral blood of healthy newborns. It has found also that there was 1.5 times increase of IL-1b in newborns with intrauterine infection in the umbilical blood in comparison with umbilical blood in healthy newborns, 3.4 times increase in IL-8 and the tendency to increase IFN-gamma.
Keywords: Pregnancy Complications, Infectious; Female; Cytokines; Cytomegalovirus Infections; Interleukin-8; novorozenec; Interferon-gamma; interleukin-4; ženské pohlaví; Herpes Simplex; fetální krev; cytokiny; lidé; Infant, Newborn; těhotenství; studie případů a kontrol; interferon gama; Fetal Blood; interleukin-8; Interleukin-4; Interleukin-1beta; Case-Control Studies; infekční komplikace v těhotenství; cytomegalovirové infekce; interleukin-1beta; Pregnancy; herpes simplex; Humans